The influence of Cr concentration on time resolution of GaAs detectors - Fedorenko, L.L.; Linnik, L.F.; Linnik, L.G.; Yusupov, M.M.; Solovyov, E.A.; Sirmulis, E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Investigated in this work were the influence of Cr dopant concentration and technological conditions of doping on photoconductivity (PhC) kinetics, dependence of PhC signal magnitude on voltage applied as well as the dynamic range of a photodetector based on semi-insulating GaAs:Cr. PhC relaxation was measured using a broadband system of registration in the picosecond pulse range, which is based on the oscillograph C7-19, CCD camera and personal computer. Mechanisms of recombination that influence on fast and slow components of the PhC signal were studied. The shortest time of PhC relaxation τ ~ 2.10⁻¹⁰ s was observed in GaAs:Cr samples for the chromium dopant concentration NCr ~ 3.10¹⁷ cm−3. We have found a linear increase of the fast component of PhC with the intensity of excitation as well as a weak dependence at small levels and saturation at the high ones of excitation for the PhC slow component.